2012
DOI: 10.3389/fpls.2012.00053
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Phloem-Mediated Long-Distance Lipid Signaling in Plants

Abstract: Plants are sessile and cannot move to appropriate hiding places or feeding grounds to escape adverse conditions. As a consequence, they evolved mechanisms to detect changes in their environment, communicate these to different organs, and adjust development accordingly. These adaptations include two long-distance transport systems which are essential in plants: the xylem and the phloem. The phloem serves as a major trafficking pathway for assimilates, viruses, RNA, plant hormones, metabolites, and proteins with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 113 publications
(145 reference statements)
2
46
0
Order By: Relevance
“…3 Although lipid compounds are present in the phloem, their role as signaling or long distance transport have not been fully elucidated. 3 Lipid analysis of canola phloem sap revealed the presence of phloem-specific fatty acids 4 and phloem exudates of Arabidopsis thaliana 5 showed the presence of unusual fatty acids that also appear to be specific to the phloem. Even though their function is unknown, it was suggested that they are involved in pathogen response or signaling.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…3 Although lipid compounds are present in the phloem, their role as signaling or long distance transport have not been fully elucidated. 3 Lipid analysis of canola phloem sap revealed the presence of phloem-specific fatty acids 4 and phloem exudates of Arabidopsis thaliana 5 showed the presence of unusual fatty acids that also appear to be specific to the phloem. Even though their function is unknown, it was suggested that they are involved in pathogen response or signaling.…”
mentioning
confidence: 99%
“…3 In plants, lipids are most often bound to proteins or phosphate groups in the cell membranes of the sieve elements. 3 Plant responses to abiotic stresses are thought to induce lipases or other cell-wall degrading enzymes which release lipids from the membranes into the phloem.…”
mentioning
confidence: 99%
See 3 more Smart Citations